2017
DOI: 10.13189/iid.2017.050101
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Extensively Drug-resistant Shigella sonnei in Bangladesh

Abstract: The objective of the study was to investigate current species distribution and growing antimicrobial resistance (AMR) of Shigella isolates for proper treatment. Shigellae, isolated from faecal samples in International Centre for Diarrhoeal Disease research, Bangladesh, Dhaka hospital in 2015, were tested for antimicrobial susceptibility by disc diffusion method to ampicillin, co-trimoxazole, ciprofloxacin, azithromycin, mecillinam, ceftriaxone/cefixime and meropenem. Extensively drug-resistant (XDR, resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In Bangladesh, many infectious diseases such as pneumonia, diarrhoea and typhoid are treated with azithromycin, an antimicrobial readily available over the counter. The observed frequent detection of ermB appeared concordant with results from studies reporting ermB detected from S. Typhi [14], S. pneumoniae [15] and Shigella sonnei [45]. Notably, we also detected other macrolide resistance genes such as ermC and ermF.…”
Section: Discussionsupporting
confidence: 91%
“…In Bangladesh, many infectious diseases such as pneumonia, diarrhoea and typhoid are treated with azithromycin, an antimicrobial readily available over the counter. The observed frequent detection of ermB appeared concordant with results from studies reporting ermB detected from S. Typhi [14], S. pneumoniae [15] and Shigella sonnei [45]. Notably, we also detected other macrolide resistance genes such as ermC and ermF.…”
Section: Discussionsupporting
confidence: 91%
“…Several vaccine candidates, developed using different techniques, are under investigation (21)(22)(23)(24)(25), but no vaccine is widely available. However, the morbidity of the disease coupled with the rise of antimicrobial resistance (26,27) urges for the introduction of an effective vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of the invasive mph (A) gene in Shigella has long been postulated by several studies from Europe, the United States, and Asia ( 12 , 14 , 15 ). One study in Bangladesh reported the presence of the mph (A) gene as one mechanism of AZM resistance in Shigella ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of the invasive mph (A) gene in Shigella has long been postulated by several studies from Europe, the United States, and Asia ( 12 , 14 , 15 ). One study in Bangladesh reported the presence of the mph (A) gene as one mechanism of AZM resistance in Shigella ( 15 ). Our investigation conveys a clear message that the mph (A) gene appears to play a key role in the rising AZM resistance among Shigella in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation